A thermodynamic bottleneck in the TCA cycle contributes to acetate overflow in Staphylococcus aureus - Nabia Shahreen; Jongsam Ahn; Adil Alsiyabi; Niaz Bahar Chowdhury; Dhananjay Shinde; Sujata S. Chaudhari; Kenneth W. Bayles; Vinai C. Thomas; Rajib Saha (mSphere)
ABSTRACT During aerobic growth, S. aureus relies on acetate overflow metabolism, a process where glucose is incompletely oxidized to acetate, for its bioenergetic needs. Acetate is not immediately captured as a carbon source and is excreted as waste by cells. The underlying factors governing acetate overflow in S. aureus have not been identified. Here, we show that acetate overflow is favored due to a thermodynamic bottleneck in the TCA cycle specifically involving the oxidation of succinate to fumarate by succinate dehydrogenase. This bottleneck reduces flux through the TCA cycle, making it more efficient for S. aureus to generate ATP via acetate overflow metabolism. Additionally, the protein allocation cost of maintaining ATP flux through the restricted TCA cycle is greater than that of acetate overflow metabolism. Finally, we show that the TCA cycle bottleneck provides S. aureus the flexibility to redirect carbon toward maintaining redox balance through lactate overflow when oxygen becomes limiting, albeit at the expense of ATP production through acetate overflow. Overall, our findings suggest that overflow metabolism offers S. aureus distinct bioenergetic advantages over a thermodynamically constrained TCA cycle, potentially supporting its commensal–pathogenic lifestyle.